2001
DOI: 10.1074/jbc.c100189200
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Resistin Expression Is Severely Suppressed in Obesity and Stimulated by Peroxisome Proliferator-activated Receptor γ Agonists

Abstract: Elevated levels of the hormone resistin, which is secreted by fat cells, are proposed to cause insulin resistance and to serve as a link between obesity and type 2 diabetes. In this report we show that resistin expression is significantly decreased in the white adipose tissue of several different models of obesity including the ob/ob, db/db, tub/tub, and KKA y mice compared with their lean counterparts. Furthermore, in response to several different classes of antidiabetic peroxisome proliferatoractivated recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
265
4
10

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(301 citation statements)
references
References 13 publications
22
265
4
10
Order By: Relevance
“…Secondly, results from studies determining expression and regulation of this adipocytokine are contradictory. Thus, severely decreased resistin mRNA levels have been observed in different mouse models of obesity and insulin resistance such as ob/ob, db/db, tub/tub, and KKA γ mice (Table 1) [60]. These findings are supported and extended by other groups indicating that resistin is down-regulated in diet-induced obesity in mice [61], in fructose-fed obese rats [62], in fa/fa rats [63], and in KK mice [64].…”
Section: Resistinsupporting
confidence: 57%
See 2 more Smart Citations
“…Secondly, results from studies determining expression and regulation of this adipocytokine are contradictory. Thus, severely decreased resistin mRNA levels have been observed in different mouse models of obesity and insulin resistance such as ob/ob, db/db, tub/tub, and KKA γ mice (Table 1) [60]. These findings are supported and extended by other groups indicating that resistin is down-regulated in diet-induced obesity in mice [61], in fructose-fed obese rats [62], in fa/fa rats [63], and in KK mice [64].…”
Section: Resistinsupporting
confidence: 57%
“…In accordance with the original observations, PPARγ-activators such as troglitazone, rosiglitazone, and darglitazone potently down-regulate resistin mRNA by approximately 80% to 90% in 3T3-L1 adipocytes in vitro [65,66] and resistin mRNA is down-regulated by 72% in db/db mice after rosiglitazone treatment [67]. In contrast, up-regulation of resistin mRNA expression has been observed after treatment of male ob/ob mice and ZDF rats with the PPARγ-agonists MC-555, rosiglitazone, and GW1929 for 7 days [60]. Similarly, consistent upregulation of resistin mRNA has been shown in white fat after treatment with the PPARγ-agonists NC-2100, pioglitazone, and troglitazone [64].…”
Section: Resistinmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of resistin amino acid sequences in mouse and human proteins is only 59% [6] and because of this incomplete homology resistin may have different physiological roles in different species [7]. In fact, studies in humans reported conflicting results, indicating decreased or increased resistin levels in obesity, opposite responses to insulin-sensitisers and contradictory correlations between resistin and markers of insulin resistance [8][9][10][11][12][13][14][15]. It has also been suggested that resistin plays a role in inflammatory conditions, because it is expressed in human macrophages [16] and because recent data have supported the existence of an independent association of resistin with the inflammatory factors IL-6 and C-reactive protein [17].…”
Section: Introductionmentioning
confidence: 99%
“…The transgenic overexpression of resistin impairs skeletal muscle glucose metabolism and promotes glucose intolerance [5]. In contrast, some reports demonstrate that a high level of resistin is not related to obesity or insulin resistance [6][7][8]. In particular, several studies with human resistin do not show any association between resistin expression and insulin resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%